Predictive Power of Financial Ratios in Business Failure: Evidence from UK Companies Using Logistic Regression - Zhao, X (2012)
THIS PAPER EXAMINES THE PREDICTIVE POWER BY FINANCIAL RATIOS IN BUSINESS FAILURE FOR A SAMPLE OF 216 UK COMPANIES BETWEEN 2003 AND 2007. EMPIRICAL RESULTS SHOW THAT THE MOST IMPORTANT DETERMINANTS OF BANKRUPTCY ARE SIZE, PROFITABILITY, LIQUIDITY AND CASH FLOW POSITION. THE PREDICTIVE POWER OF THE LOGISTIC MODEL IS REASONABLY HIGH OF OVERALL FIVE SAMPLE YEARS PRIOR TO BUSINESS FAILURE.